Ferrocement in recreational and public health development - Megat Mohd Noor, Megat Johari; Jusoh, Ahmad; Jaafar, Mohd Salleh (1989)
Ferrocement has the versatility such that can be 'sculptured' or shaped into numerous fascinating structures and objects for very wide applications. It normally composes of steel meshes and bars embedded within the matrix of cement mortar. It also has the ability to be combined with other materials such as fibers. Ferrocement primarily differ from conventional reinforced or prestressed concrete by the maner in which the reinforcing elements are dispersed and arranged. The beauty of this material is that it can be formed into a thin structure to a minimum of 20 mm thickness provided skill workmanship is available. The exposure of this technology to engineers in general is rather minimal in the Malaysian contact and many are skeptical about it. The potential is not exploited for it being unconventional in nature. Its ability to compete or use as a cheaper alternative and yet a promising technology in ensuring improved living standard and environmental quality must not be neglected. Ferrocement has a role in providing a safe and beautified environment which can ensure the success in attracting visitors to the scene. The paper discusses about the applicability and the development of ferrocement in the Malaysian scene with respect to recreation and public health improvement.